LYMPHOCYTIC HYPOPHYSITIS MASQUERADING AS PITUITARY MACROADENOMA WITH SUPRASELLAR EXTENSION - Ng, Ym; Vethakkan, SR; Lim, LL; Paramasivam, SS; Ibrahim, L; Lim, QH; Ratnasingam, J (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Autoimmune hypophysitis mimics the more common non-secreting pituitary adenomas. The diagnosis can only be confirmed with certainty only through histology examination of the pituitary gland. Studies have shown up to 40% of patients with hypophysitis are misdiagnosed as having pituitary macroadenoma and undergo unnecessary surgery. RESULTS A man suffered from daily headache, nausea, lethargy, loss of weight and blurred vision for one year. He was thirsty all the time and drank eight liters of fluid in a day with bothersome nocturia. He was intolerant of cold weather and had constipation and noticed dry skin. His libido was low. His progressive reduction in effort tolerance resulted in him unable to continue working. On examination, he was of medium built with bradycardia and dry skin. Visual confrontation revealed bitemporal hemianopia. Laboratory investigations revealed central hypothyroidism, hypogonadotropic hypogonadism, central hypocortisolism and a compensated cranial diabetes insipidus. Imaging revealed a heterogeneously enhancing mass in the sella measuring 19 x 12 x 12 mm with suprasellar extension causing mass effect into the optic chiasm. The pituitar ytalk was not visualized. Hormonal replacement was commenced. He underwent trans-sphenoidal surgery and histopathology showed chronic hypophysitis. He was then pulsed with steroid and had clinical improvement. CONCLUSION Differentiating autoimmune hypophysitis from nonsecreting pituitary adenoma before surgery would greatly benefit the patient. It avoids the possible complications of surgery. Furthermore, autoimmune hypophysitis can be successfully treated with medications. Another important learning point from this case is to highly suspect hypophysitis in a patient who has cranial diabetes insipidus even before any pituitary surgery.